Analisis Strategi Segmentasi, Targeting, dan Postioning Eiger: Analysis of Eiger's Segmentation, Targeting and Positioning Strategies - Muhammad Zaky Yamin; Agus Rahayu; Puspo Dewi Dirgantari (Experimental Student Experiences, 2022)
The purpose of this research is to find out eiger's segmentation, targeting, and positioning strategies in fulfilling the needs and desires of consumers in doing outdoor activities. The research method used to achieve the research objectives was a qualitative method, the data collection method used systematic literature review. The results showed, (1) Segmentation, Eiger's market segment is consumers who are happy with outdoor activities and consumers who are happy with the adventurous style, this is for clothing products. For products from Eiger Coffee, the segmentation is focused on consumers who are looking for coffee with good quality but at a low price. (2) The target market targeted by Eiger is consumers who like adventure, and or consumers who like the style of an adventurer, this is for clothing products. For products from Eiger Coffee, Eiger coffee targets its products for coffee lovers who are looking for the best taste and quality (3) Positioning, positioning according to benefits. As mentioned above, Eiger products provide comfort when worn, besides that Eiger products have good material strength so that Eiger products are resistant and durable. Second, Eiger has clothing and coffee products that are relatively more expensive than competitors in the same industry.